PENGARUH E-WOM DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA BASO ACI AKANG - Alda Agnesia Putri (2021)
This research is quantitative and objectives to determine the effect of E-WOM and brand image on purchasing decisions. The research population is Baso Aci Akang consumers who are in the West Jakarta area where the sample used is 100 respondents, with non-probability sampling methods, especially purposive sampling. Data was collected by distributing online questionnaires in the form of google forms. The data analysis technique used is descriptive analysis and inferential analysis with the analytical tool used is SmartPLS 3.3.3. The results of this research indicate that (1) E-WOM has a significant influence on purchasing decisions of 0.391 (2) brand image has a significant influence on purchasing decisions with a value of 0.368.